2017
DOI: 10.1038/s41598-017-06978-3
|View full text |Cite
|
Sign up to set email alerts
|

Troponin I and T in relation to cardiac injury detected with electrocardiography in a population-based cohort - The Maastricht Study

Abstract: Interest in high-sensitivity cardiac troponin I(hs-cTnI) and T(hs-cTnT) has expanded from acute cardiac care to cardiovascular disease(CVD) risk stratification. Whether hs-cTnI and hs-cTnT are interchangeable in the ambulant setting is largely unexplored. Cardiac injury is a mechanism that may underlie the associations between troponin levels and mortality in the general population. In the population-based Maastricht Study, we assessed the correlation and concordance between hs-cTnI and hs-cTnT. Multiple regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…Recent publications 47 , 48 have shown that the nonparametric approach in combination with a conservative treatment of outliers is the preferred method for determination of the 99 th percentile URL for hs-cTn. The 99 th percentile values were determined by 1-tailed non-parametric statistics according to CLSI guidelines 49 – 51 with no exclusion of outliers. Continuous variables were assessed for normal distribution using the Shapiro-Wilk test.…”
Section: Methodsmentioning
confidence: 99%
“…Recent publications 47 , 48 have shown that the nonparametric approach in combination with a conservative treatment of outliers is the preferred method for determination of the 99 th percentile URL for hs-cTn. The 99 th percentile values were determined by 1-tailed non-parametric statistics according to CLSI guidelines 49 – 51 with no exclusion of outliers. Continuous variables were assessed for normal distribution using the Shapiro-Wilk test.…”
Section: Methodsmentioning
confidence: 99%
“…31,32 However, our finding is consistent with studies in individuals without known coronary artery disease and even those with stable disease. 4,33,34 Biological etiologies for observed differences between hs-TnI and hs-TnT may reflect distinctions in structure, kinetics, and clearance. 33,[35][36][37][38][39][40] We found that individuals with high hs-TnI but lower hs-TnT levels, when compared with those with lower hs-TnI and high hs-TnT, had more high-risk features, including hypertension, hyperlipidemia, smoking, and left ventricular hypertrophy, but had better renal function.…”
Section: Discussionmentioning
confidence: 99%
“…The most likely explanation for this finding therefore is the biological non-equivalence of 26 ng/L for hs-cTnI versus 14ng/L for hs-cTnT as previously documented in two large studies (15,16). The biological equivalent hs-cTnI concentration corresponding to the 99 th percentile for hs-cTnT was about half the approved 99 th percentile for hs-cTnI in these studies (15,16). This major discrepancy in the currently recommended 99 th -percentiles became also evident in this dataset: diagnostic accuracies for NSTEMI provided by early absolute changes of hs-cTn within 1-hour, alone or in combination with hs-cTn concentrations at presentation, provided very high and similar diagnostic accuracy in patients with low ACSprobability as compared to the other strata.…”
Section: Discussionmentioning
confidence: 69%
“…At first glance, this is surprising as both assays seem to have comparable diagnostic accuracy for AMI (14), and hs-cTnI seems to have even higher analytical sensitivity as compared to hs-cTnT (11). The most likely explanation for this finding therefore is the biological non-equivalence of 26 ng/L for hs-cTnI versus 14ng/L for hs-cTnT as previously documented in two large studies (15,16). The biological equivalent hs-cTnI concentration corresponding to the 99 th percentile for hs-cTnT was about half the approved 99 th percentile for hs-cTnI in these studies (15,16).…”
Section: Discussionmentioning
confidence: 80%